Australia's contribution to global immunisation - Tilman A. Ruff; Kate Taylor; Terry Nolan (Australian and New Zealand Journal of Public Health, 2012)
Abstract Objective : To review Australian contributions to global immunisation. Approach : We summarise Australian scientific and program contributions to vaccines and global immunisation, describe key developments and strengths in Australia's national immunisation program, and outline how both of these can link with Australia's increasing international development budget to build Australia's future contribution to global immunisation. Conclusions : Australian contributions to vaccines and immunisation have been substantial, and Australia offers a range of good practices in its domestic and development approaches. There are major opportunities to build on this strong track record. These include committing to help roll out important new life‐saving vaccines against pneumococcal disease, rotavirus and human papilloma virus (HPV) to the children who need them most, but whose communities can least afford them. Implications : Australia is one of a few countries expanding their aid budgets towards 0.7% development assistance and other development commitments. Given the importance of immunisation to health gains, Australia is well placed to expand its investment in immunisation within its development portfolio. The GAVI Alliance is the best‐established global mechanism to do this. Additionally, however, Australia could harness other national and regional mechanisms to support low and middle‐income countries, thereby complementing GAVI's focus and global needs.